Relevance of assembly-activating protein for adeno-associated virus vector production and capsid protein stability in mammalian and insect cells - Große, Stefanie; Börner, Kathleen; Fakhiri, Julia; Laketa, Vibor; Wiedtke, Ellen; Gunkel, Manuel; Grimm, Dirk (Journal of virology, 2017)
The discovery that adeno-associated virus 2 (AAV2) encodes an eighth protein, called assembly-activating protein (AAP), transformed our understanding of wild-type AAV biology. Concurrently, it raised questions about the role of AAP during production of recombinant vectors based on natural or molecularly engineered AAV capsids. Here, we show that AAP is indeed essential for generation of functional recombinant AAV2 vectors in both mammalian and insect cell-based vector production systems. Surprisingly, we observed that AAV2 capsid proteins VP1 to -3 are unstable in the absence of AAP2, likely due to rapid proteasomal degradation. Inhibition of the proteasome led to an increase of intracellular VP1 to -3 but neither triggered assembly of functional capsids nor promoted nuclear localization of the capsid proteins. Together, this underscores the crucial and unique role of AAP in the AAV life cycle, where it rapidly chaperones capsid assembly, thus preventing degradation of free capsid proteins. An expanded analysis comprising nine alternative AAV serotypes (1, 3 to 9, and rh10) showed that vector production always depends on the presence of AAP, with the exceptions of AAV4 and AAV5, which exhibited AAP-independent, albeit low-level, particle assembly. Interestingly, AAPs from all 10 serotypes could cross-complement AAP-depleted helper plasmids during vector production, despite there being distinct intracellular AAP localization patterns. These were most pronounced for AAP4 and AAP5, congruent with their inability to rescue an AAV2/AAP2 knockout. We conclude that AAP is key for assembly of genuine capsids from at least 10 different AAV serotypes, which has implications for vectors derived from wild-type or synthetic AAV capsids. IMPORTANCE: Assembly of adeno-associated virus 2 (AAV2) is regulated by the assembly-activating protein (AAP), whose open reading frame overlaps with that of the viral capsid proteins. As the majority of evidence was obtained using virus-like particles composed solely of the major capsid protein VP3, AAP's role in and relevance for assembly of genuine AAV capsids have remained largely unclear. Thus, we established a trans-complementation assay permitting assessment of AAP functionality during production of recombinant vectors based on complete AAV capsids and derived from any serotype. We find that AAP is indeed a critical factor not only for AAV2, but also for generation of vectors derived from nine other AAV serotypes. Moreover, we identify a new role of AAP in maintaining capsid protein stability in mammalian and insect cells. Thereby, our study expands our current understanding of AAV/AAP biology, and it concomitantly provides insights into the importance of AAP for AAV vector production.
Posted online 2 August 2017
Gesehen am 08.06.2018